Karakteristik Industrialisasi Modern Berbasis Revolusi Industri 4.0 dalam Menghadapi Persaingan Industri Global Digital - Farida Sasi Febrianty; Mohammad Romadhoni Adi Setiawan; Muhammad Yasin (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2026)
Modern industrialization is characterized by the integration of digital technology, automation, and global connectivity into industrial activities. This study aims to analyze the characteristics of modern industrialization and examine its impact on economic and social development. The research employs a descriptive qualitative approach using secondary data collected from scientific journals, books, and government reports. The findings indicate that technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), and automated production systems significantly enhance production efficiency, product quality, and industrial competitiveness. In addition, digital transformation supports faster communication, more accurate data management, and broader market access for industries. However, modern industrialization also presents several challenges, including labor displacement due to automation, widening skill gaps, and unequal access to technology. These conditions require governments and industries to improve human resource quality through education and training programs. Adaptive industrial policies and sustainable development strategies are also necessary to ensure that industrial progress provides balanced economic and social benefits.